2021
DOI: 10.1101/2021.11.10.468024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting efficiency of writing short sequences into the genome using prime editing

Abstract: SUMMARYShort sequences can be precisely written into a selected genomic target using prime editing. This ability facilitates protein tagging, correction of pathogenic deletions, and many other exciting applications. However, it remains unclear what types of sequences prime editors can easily insert, and how to choose optimal reagents for a desired outcome. To characterize features that influence insertion efficiency, we designed a library of 2,666 sequences up to 69 nt in length and measured the frequency of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Together with recent reports 39,40 , our data shed new light on the molecular mechanism of a new and highly promising genome editing technology. We have shown that the MMR pathway inhibits PE efficiency by physically localising to edit sites and promoting their reversion to non-edited sequences.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Together with recent reports 39,40 , our data shed new light on the molecular mechanism of a new and highly promising genome editing technology. We have shown that the MMR pathway inhibits PE efficiency by physically localising to edit sites and promoting their reversion to non-edited sequences.…”
Section: Discussionsupporting
confidence: 76%
“…Chen and colleagues showed that MMR involvement decreases with increasing indel size and that G/C to C/G edits, which form C:C mismatches, are less frequently removed by MMR factors 39 . Koeppel and colleagues systematically measured the insertion efficiency of indels ranging from 1 to 69 bp in length 40 . The authors observed an overall increase of insertion efficiency upon MMR depletion, with the greatest difference seen for indels 1-4 bp long.…”
Section: Discussionmentioning
confidence: 99%
“…Together with recent reports (Chen et al, 2021; Koeppel et al, 2021), our data shed new light on the molecular mechanism of a new and highly promising genome editing technology. We have shown that the MMR pathway inhibits PE efficiency by physically localising to edit sites and promoting their reversion to non-edited sequences.…”
Section: Discussionsupporting
confidence: 78%
“…Chen and colleagues showed that MMR involvement decreases with increasing indel size and that G/C to C/G edits, which form C:C mismatches, are less frequently removed by MMR factors (Chen et al, 2021). Koeppel and colleagues systematically measured the insertion efficiency of indels ranging from 1-69 bp in length (Koeppel et al, 2021). The authors observed an overall increase of insertion efficiency upon MMR depletion, with the greatest difference seen for indels 1-4 bp long.…”
Section: Discussionmentioning
confidence: 99%
“…We then transfected pegRNAs encoding random 6-bp insertions. The use of random insertions allowed us to minimize potential bias caused by the insertion sequence itself 49 , as well as to distinguish real editing outcomes (in situ transcribed in nuclei) from ambient transcripts. After 3-4 days, perturbed cells derived from the two clones were mixed at a 1:1 ratio and profiled leveraging a modified sci-RNA-seq3 workflow (Fig.…”
Section: Strategy For Investigating the Chromatin Context-dependencie...mentioning
confidence: 99%